Chinese Classical Music Lowers Blood Pressure and Improves Left Ventricular Hypertrophy in Spontaneously Hypertensive Rats - Li, Jingyuan; Yang, Zhi; Zhang, Chunmei; Hu, Yang; Li, Hongxuan; Zhang, Meng; Bu, Peili; Wang, Shuangxi; Zhang, Cheng; Li, Wenjing (Frontiers in Pharmacology, 2022)
High blood pressure (BP) plays an important role in the pathogenesis and development of cardiovascular diseases and multi-organ damages. Music has been well known to elicit emotional changes, such as anxiolytic effects. However, whether music therapy lowers BP in spontaneously hypertensive rats (SHR) and the potential mechanism remains unknown. SHRs were respectively expose to white noise (WN), Western music (WM), Chinese classic music (CCM), rocking music (RM), and bisoprolol treatment. Exposures to CCM and RM significantly lowered BPs in SHRs and the decrease extent of CCM group is greater than that of RM group. The effects of CCM therapy on lowering systemic BPs is comparable to that of bisoprolol at the dose of low to medium. Combination of CCM treatment with bisoprolol further improved systemic BPs and myocardial hypertrophy in SHRs, compared to CCM treatment or bisoprolol alone. Furthermore, IHC and WB analysis indicated that CCM therapy inhibited the β1/cAMP/PKA and α1/PLC/PKC signalings, but didn’t alter the β2/PI3K/Akt signaling. Above all, CCM therapy lowers systemic BPs and alleviates myocardial hypertrophy in hypertensive rats, which may be caused by the inhibitions of β1/cAMP/PKA and α1/PLC/PKC signalings.